Peas and carrots - Davis, Tanita S. (Alfred A. Knopf, 2016)
After her mother is arrested, fifteen-year-old Dess is sent to live with the foster family that took in her baby brother several years before, and although she and her new foster sister, Hope, clash immediately, they soon realize they have much in common.